2006
DOI: 10.1200/jco.2005.05.1912
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Urokinase-Type Plasminogen Activator mRNA Determines Adverse Prognosis in ErbB2-Positive Primary Breast Cancer

Abstract: After evaluation of 898 breast cancer patients, uPA mRNA expression emerged as a powerful prognostic indicator in ErbB2-positive tumors. These results were consistent among three independent study populations assayed by different techniques, including qrt-PCR and two microarray platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 28 publications
7
54
0
3
Order By: Relevance
“…The amplicon lengths of the QPCR assays for uPA and PAI-1 were minimized as far as possible to potentially enable quantification of partially fragmented mRNA extracted from formalin-fixed, paraffinembedded tissue (38). Recently, several QPCR assays for determination of uPA and/or PAI-1 mRNA expression have been introduced with rather large amplicon sizes (13)(14)(15)17,18,39,40). In contrast, our newly developed QPCR assays use amplicon lengths ranging from 103 to 132 base pairs, the shortest uPA/PAI-1 QPCR-derived cDNA fragments described so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplicon lengths of the QPCR assays for uPA and PAI-1 were minimized as far as possible to potentially enable quantification of partially fragmented mRNA extracted from formalin-fixed, paraffinembedded tissue (38). Recently, several QPCR assays for determination of uPA and/or PAI-1 mRNA expression have been introduced with rather large amplicon sizes (13)(14)(15)17,18,39,40). In contrast, our newly developed QPCR assays use amplicon lengths ranging from 103 to 132 base pairs, the shortest uPA/PAI-1 QPCR-derived cDNA fragments described so far.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published data regarding the clinical impact of uPA and PAI-1 in breast cancer have been collected determining the uPA and/or PAI-1 antigen content by ELISA in cytosol extracts or detergent-released membrane extracts of freshfrozen breast cancer specimens. On the other hand, mRNA expression of uPA and/or PAI-1 in breast cancer samples in relation to patient outcome has been analyzed only in few studies (13)(14)(15)(16)(17). Furthermore, systematic studies with the objective to compare uPA/PAI-1 mRNA expression values with uPA/PAI-1 antigen levels in tumor tissue extracts determined by ELISA are rare, and patient numbers are small (13,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, T/t-common could modulate the expression of several pro-and antiangio- genic factors in SK-OV-3 cells (Figures 4 and 5), and some of them (such as VEGF-A, IL-8, matrix metalloproteinase-2, urokinase-type plasminogen activator and TSP-1) have been shown to be the downstream targets of HER2. 9,10,28,37,38 Thirdly, T/t-common could reproduce some of the results (such as downregulation of VEGF-A and IL-8 and upregulation of TSP-1) obtained by expressing HER2 short interfering RNA in HER2-overexpressing cancer cells. 9,27 Fourthly, T/t-common could inhibit the angiogenesis-inducing activity of the HER2-overexpressing SK-OV-3 ovarian cancer cells, but not that of the HER2 low-expressing OVCAR-3 ovarian cancer cells (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 83%
“…These data are consistent with the previous reports that VEGF-A, IL-8, urokinase-type plasminogen activator and matrix metalloproteinase-2 are upregulated, whereas TSP-1 is downregulated by HER2. 9,10,28,37,38 The ability to target multiple pro-and antiangiogenic factors in HER2-overexpressing cancer cells makes T/t-common a potentially better choice than single-target antiangiogenic agents, such as anti-VEGF antibody bevacizumab, for treating HER2-overexpressing cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A French group also found a weak positive correlation between uPA/PAI-1 and HER-2 [29]. The study by Urban et al indicates that overexpression of uPA mRNA levels in HER-2 positive breast cancer determines a worse outcome of the disease [30]. On the other hand, Harbeck et al demonstrated that uPA/PAI-1 and HER-2 gave independent information on disease-free survival in lymph node-negative breast cancer patients [31] with a similar finding described by Konecny et al [32] and by Zemzuoum et al [33].…”
Section: Discussionmentioning
confidence: 96%